Hippocrates' Maze ethical explorations of the medical labyrinth. - Lindemann Nelson, James (Totowa Rowman & Littlefield, 2003)
To contain the Minotaur, the ancient artificer Daedalus crafted a maze so intricate that it bewildered even its maker. Contemporary medicine-'Hippocrates' Maze-is every bit as bewildering, so much so that a new and distinct field, bioethics, has been created to help professional caregivers, patients, and families navigate their way through it. In Nelson's typically inviting and graceful style, the essays collected in Hippocrates' Maze explore the labyrinth of contemporary health care, and arrive at some unusual findings about death and decisionmaking, justice and families, cloning and kinship, and organ donation and intimacy. However, the book's most distinctive conclusions concern bioethics itself: the field is not best seen solely as a source of good advice to doctors, but rather as a way of better understanding our humanity.
7. Cloning, Families, and the Reproduction of Persons
Keywords: Medical ethics